Answer:
[tex]k = \frac{2}{9}, k=\frac{-2}{9}[/tex]
Step-by-step explanation:
The first case is a special case of the second one, so we will solve the question for the second case first.
Consider [tex]y = A\sin(kt) + B\cos(kt)[/tex]. Using the properties of derivatives and the derivatives of trigonometric functions we get that
[tex]y' = A\cdot k \cos(kt)- B \cdot k \sin(kt) = k (A\cos(kt)-B\sin(kt))[/tex]
[tex]y'' = k(-A\cdot k \sin(kt)-B\cdot k \cos(kt)) = -k^2(y)[/tex]
We have the equation [tex]81y''=-4y[/tex]. Note that since [tex]y'' = -k^2y[/tex]then we have the equation
[tex]-k^2 81y=-4y[/tex],
which implies that [tex]k^2 = \frac{4}{81}[/tex]. Then, [tex]k=\pm\frac{2}{9}[/tex]
Note that in this case, the value of k doesn't depend on the values of A and B. So, it applies to every value of A and B. The first case is included, since it is the case in which A=0 and B=1.